Implementasi Kaidah Ushuliyyah Dalam Transaksi Keuangan Modern: Bunga Bank Dalam Perbankan Syariah - Ramadani, Tasya Almutia; Kamila, Selma Zahra; Ikhsan, Akmal; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Ushuliyyah rules are the basis for understanding Islamic law which is very important to study. This article aims to explain the main concepts in ushuliyyah rules such as Manthuq and Mafhum, Dzahir and Muawwal, Nasakh, and Muradif and Musytarak. The research method uses a qualitative approach with literature study as the main data source. Research findings show that a deep understanding of the rules of ushuliyyah is very crucial for the development of dynamic and contextual Islamic fiqh. This study finds that the application of ushuliyyah rules in contemporary cases, such as legal interpretations of modern financial transactions, provides relevant and contextual solutions. These conclusions provide an important academic contribution to the study of ushul fiqh as well as offering suggestions for further research in this area.